Effects of Harvesting Period on Phytochemicals of Wheatgrass (Triticum aestivum, WK 1204 Variety) - Babita Adhikari; Sanil Joshi; Bunty Maskey (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Wheatgrass is a plethora of essential phytochemicals considered to exhibit numerous benefits on human health. Therefore, the study of phytochemicals with varying stages of growth is essential. This study aims to determine the optimum harvesting period of wheatgrass based on its phytochemical content. During the growth of wheat seed (WK 1204 variety), the phytochemicals such as chlorophyll, total phenol content, flavonoids and tannins were extracted by 80% acetone and 80% methanol from wheatgrass harvested on days 6, 7, 8, 9 12 and 15, respectively. 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, chlorophyll and flavonoid contents significantly (p<0.05) increased and reached the maximum level on day 9. Total phenol content was found to be increasing significantly (p<0.05), while the tannin content was decreasing considerably (p<0.05) on day 15. The optimum harvesting period was found on day 9. The DPPH radical scavenging activity, chlorophyll and flavonoid content significantly (p<0.05) increased and reached the maximum level, i.e., 92.27±1.92%, 6.63±0.053 mg g-1 and 183.64±33.49 mg QE g-1, respectively, on day 9 of cultivation. The total phenol content was found to be increasing significantly (p<0.05) from 291.67±5.69 mg GAE g-1 on day 6 to 446.67±5.77 mg GAE g-1 on day 15, while the tannin content was declining significantly (p<0.05) from 11.74±0.29 mg GAE g-1 on days 6, 7 and so on to 3.36±0.47 mg GAE g-1 on day 15. Therefore, the optimum harvesting period of wheatgrass was found to be day 9 in terms of phytochemical analysis.